2015
DOI: 10.1073/pnas.1519528112
|View full text |Cite
|
Sign up to set email alerts
|

Xist imprinting is promoted by the hemizygous (unpaired) state in the male germ line

Abstract: This contribution is part of the special series of Inaugural Articles by members of the National Academy of Sciences elected in 2015. Contributed by Jeannie T. Lee, October 1, 2015 (sent for review July 29, 2015; reviewed by Nora Engel and Kathrin Plath)The long noncoding X-inactivation-specific transcript (Xist gene) is responsible for mammalian X-chromosome dosage compensation between the sexes, the process by which one of the two X chromosomes is inactivated in the female soma. Xist is essential for both th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 61 publications
0
25
0
Order By: Relevance
“…A similar study using single--copy transgenes has previously concluded that this is evidence that the imposed imprint is exclusively a maternal, repressive one and that Xist is expressed by default when inherited paternally without the need of a paternal imprint [36]. In the more recent study [44], however, in which multicopy transgenes were used, a different conclusion was drawn, which implied both a maternal and a paternal imprint (Fig. 1).…”
Section: Imprinted XCImentioning
confidence: 66%
See 4 more Smart Citations
“…A similar study using single--copy transgenes has previously concluded that this is evidence that the imposed imprint is exclusively a maternal, repressive one and that Xist is expressed by default when inherited paternally without the need of a paternal imprint [36]. In the more recent study [44], however, in which multicopy transgenes were used, a different conclusion was drawn, which implied both a maternal and a paternal imprint (Fig. 1).…”
Section: Imprinted XCImentioning
confidence: 66%
“…However, it seems that H3K9me3 is not the primary imprinting mark, as there is no difference in H3K9me3 at the Xist promoter before and after oocyte growth, when the imprint is established [43]. On the other hand, the Xist locus appears more condensed after imprint establishment during oocyte growth, which could influence Xist repression on the Xm, although the opposite has been postulated for Xist expression from the Xp (see below [44] Another critical regulator with a function in imprinted XCI is Tsix, the noncoding antisense regulator of Xist. Tsix is expressed from the Xm during imprinted XCI and mouse embryos with a Tsix mutation on the Xm express Xist from both the paternal and maternal X--chromosomes in extraembryonic tissues and die during early postimplantation development [45,46].…”
Section: Imprinted XCImentioning
confidence: 99%
See 3 more Smart Citations